Situational Social Support and Relapse: An Exploration of Compulsory Drug Abuse Treatment Effect in China - Xiong, Haiyan (International journal of offender therapy and comparative criminology, 2019)
The present study explores situational social support of drug abusers during compulsory rehabilitation and provides a preliminary estimation of relationship between social support and relapse. Links between social support and relapse are examined in a study of drug abusers accepting coercive detoxification and rehabilitation treatment, and self-reported relapse in the following 6 months (N = 535). External and internal social support with abstinence-specific support inclusive are investigated. With certain demographic variables and risk-related variables controlled, greater special type of external social support (as measured by number of children) predicts a lower risk of relapse, which means better effect of compulsory rehabilitation. Participation into some of the institutional programs and experienced personal conflicts for abstinence show no statistically significant with relapse risk.